Fall Detection using Sensors on a Smartphone - Priswanto, Budi; Haryono, Haryono (Politeknik Ganesha Medan, 2022)
A work accident on a technician causes injury. When doing work, even though the technician is equipped with work safety, there are still factors that can cause accidents intentionally or unintentionally. The development of technology is now more advanced. Now the industrial revolution has reached the era of 4.0. Its progress is accompanied by information technology that is growing very rapidly. Many internets of things devices can already be used in everyday life. In today's life, the use of IoT devices has become a habit of today's modern society. For example, to travel using public transportation, there are many mobile apps that are connected to transportation providers. Including trade, the number of marketplaces has caused the growth of smartphones to be very fast. Smartphones are now equipped with many sensors, ranging from GPS sensors, wi-fi sensors, temperature sensors, and various sensors. Often the technicians in charge of climbing towers or heights are never caught by management or project leaders. Even though this causes losses both losses for technicians and losses for management. Therefore, how to monitor the technicians to be careful in carrying out their duties. Android smartphone devices have many sensors. Sensors in Android are used as a fall detection tool. By using Android sensors, the use of Internet of Thing sensors on smartphones will produce very useful monitoring tools. The use of Flutter framework as a medium for utilizing the accelerometer sensor and gyroscope sensor as a fall detection tool. This study aims to create a prototype of a fall detection application system.